The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/metabo10030084
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Fingerprints of Emotional Body Odor

Abstract: Chemical communication is common among animals. In humans, the chemical basis of social communication has remained a black box, despite psychological and neural research showing distinctive physiological, behavioral, and neural consequences of body odors emitted during emotional states like fear and happiness. We used a multidisciplinary approach to examine whether molecular cues could be associated with an emotional state in the emitter. Our research revealed that the volatile molecules transmitting different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 62 publications
(83 reference statements)
1
37
1
1
Order By: Relevance
“…Another necessity [47] is then to characterize molecule quality (actual molecule identities) aside from quantity, to test if the same doses of fear sweat and neutral sweat are qualitatively different, and whether higher doses of fear sweat are represented by 'more of the same' molecules that would also be found in lower doses of fear sweat. If such olfactory signatures of fear (degree) exist [48], how consistent are they across circumstances, and how broadly are these signatures endorsed by the human species (e.g. across gender, cultures, lifespan)?…”
Section: Discussionmentioning
confidence: 99%
“…Another necessity [47] is then to characterize molecule quality (actual molecule identities) aside from quantity, to test if the same doses of fear sweat and neutral sweat are qualitatively different, and whether higher doses of fear sweat are represented by 'more of the same' molecules that would also be found in lower doses of fear sweat. If such olfactory signatures of fear (degree) exist [48], how consistent are they across circumstances, and how broadly are these signatures endorsed by the human species (e.g. across gender, cultures, lifespan)?…”
Section: Discussionmentioning
confidence: 99%
“…tradition. Although several psychological studies have revealed systematic patterns in the behaviors of senders and recipients (in relatively sterile, uniform settings), the chemical message driving this coupling has generally remained enciphered (but see Penn et al, 2007;Smeets et al, 2020). Lessons can be learned from the animal literature, where the combination of rigorous behavioral experiments (bioassay) and chemical analysis (isolating, identifying, and synthesizing the bioactive substance to recreate the bioassay-behavior) forms the golden standard to detect a common chemical "language" for a species: pheromones (Wyatt, 2015(Wyatt, , 2020.…”
Section: Problem Iii: Unidisciplinary Researchmentioning
confidence: 99%
“…Other studies found chemical markers suggestive of fear (and happiness). Potential chemical markers for fear were identified by in armpit odor (Smeets et al, 2020), stress levels were also expressed in a person's breath (Preti et al, 2019; acetone, isoprene, dimethyl sulfide), and in a creative field study, (Williams et al, 2016) showed that scary and funny film events reliably changed the emission of molecules from cinema audiences. Taken together, these multidisciplinary studies show the potential for social information to be encoded in a person's smell in predictable ways, thus jumpstarting a sociochemistry approach to identify a common smell language.…”
Section: Multidisciplinary Approach: Deciphering the Alphabet Of Socimentioning
confidence: 99%
See 2 more Smart Citations